Bifurcations and membrane excitability of a two-dimensional neural model. (June 2015) - Liu, Xuanliang; Zhao, Chuanli
Abstract: In this paper, we investigate the dynamical behaviors of a two-dimensional Hodgkin–Huxley like neural model. By using bifurcation methods and numerical simulations, we study the bifurcations and membrane excitability in the neural model. We give the two-parameter and one-parameter bifurcation diagrams and pay much attention to the emergence of periodic solutions and multistability. Different classes of membrane excitability are obtained by the bifurcation analyses and the frequency-current curves. We also show that the neural model possesses bistability and tristability.